2016
DOI: 10.1093/pan/mpw006
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Preferences Using Roll Call Votes in Parliamentary Systems

Abstract: Models of ideal point estimation usually build on the assumption of spatial preferences. This ignores legislators' non-policy incentives and is thus likely to produce implausible results for many legislatures. We study this problem in parliamentary systems and develop a model of roll call voting that considers both thepolicyand the non-policy,tacticalincentives of legislators. We go on to show how the relative weight of these policy and tactical incentives is influenced by the identity of the mover and charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 69 publications
1
27
0
Order By: Relevance
“…11 A list of party-switchers can be found in Appendix F. Others have suggested that voting patterns may differ depending on the nature of the division, when it occurs within the parliamentary agenda (Bräuninger, Müller and Stecker 2016;Coman 2012), and whether a vote is recorded (Hug 2010). 12 Using the extensive division titles provided by www.theyworkforyou.com for the later period of our study (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) we identify where and 12 Recent advances in the literature on roll call votes have focussed on analysing and accounting for selection effects (Carrubba, Gabel and Hug 2008;Hug 2010;Rosas, Shomer and Haptonstahl 2015).…”
Section: Data On Divisions Defections and Debatesmentioning
confidence: 99%
“…11 A list of party-switchers can be found in Appendix F. Others have suggested that voting patterns may differ depending on the nature of the division, when it occurs within the parliamentary agenda (Bräuninger, Müller and Stecker 2016;Coman 2012), and whether a vote is recorded (Hug 2010). 12 Using the extensive division titles provided by www.theyworkforyou.com for the later period of our study (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) we identify where and 12 Recent advances in the literature on roll call votes have focussed on analysing and accounting for selection effects (Carrubba, Gabel and Hug 2008;Hug 2010;Rosas, Shomer and Haptonstahl 2015).…”
Section: Data On Divisions Defections and Debatesmentioning
confidence: 99%
“…The ideal point model's purpose is to compress the large amount of roll-call votes in a parliament down into a single-dimensional score that can represent each legislator's political position relative to every other legislator. In our case, we examine party-level and cleavagelevel ideal points rather than individual ideal points as most of the variation in ideal points in parliamentary systems happens at the party level rather than the individual level (Bräuninger, Müller, and Stecker 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The two rival theories, as advanced in the relevant literature and formalized above, remain largely silent on the role of ideology in career politicians' voting behavior. Their focus on the strategic (or “non‐spatial”) motivation for legislative behavior can, in part, be justified by the recurring finding that nonideological considerations often play a more important role in voting behavior in parliamentary systems (e.g., Bräuninger, Müller, and Stecker ; Dewan and Spirling ; Kam , ). To paint a more complete picture of the behavioral incentives of career and non‐career politicians, however, I also consider a preference‐based explanatory account.…”
Section: Party Loyalty Of Career Politicians: the Theoretical Argumentsmentioning
confidence: 99%